The Effect of the Light of the Container ad the Dose of Tubifex sp. On Growth and Survival of Asian Redtail Catfish (Hemibagrus nemurus) larvae - Desi Sukmawati; Sukendi Sukendi; Netti Aryani (Jurnal Akuakultur SEBATIN, 2022)
The purpose of this research was to determine the effect of light on the container and the dose of Tubifex sp. on the growth and survival of Asian Redtail Catfish larvae and determine the treatment with the best interaction results. This research method was experimental with a Factorial Completely Randomized Design with two 2 factors, the first was light container consisting of 2 levels, namely light container and dark container. While the second factor was the dose of Tubifex sp. consisted of 3 levels namely 40%, 60%, and 80%. There are 6 combinations with 3 replications. The treatments consisted of: 1) WtP40 (bright container and dose of Tubifex sp. 40%), 2) WtP60 (bright container and dose of Tubifex sp. 60%), 3) WtP80 (bright container and dose of Tubifex sp. 80%) 4) WgP40 (dark container and dose of Tubifex sp. 40%), 5) WgP60 (dark container and dose of Tubifex sp. 60%), and 6) WgP80 (dark container and dose of Tubifex sp. 80%). The results showed that the light of the container and the dose of Tubifex sp. Had significant effect and statistical test results (Student Newman Keuls P > 0.05) on the growth and survival of baung fish larvae. The best treatment was WgP80 with an absolute weight of 1.94 g, absolute length 6.2 cm, LPS 16.16%, feed efficiency 25.49%, and survival rate 93.21%. Water quality parameters during the research were measured by the results of temperatures ranging from 27.0-28.2 , pH ranging from 6.3-7.2, and DO ranging from 4.0-5.4 mg/l.